Structure, Prohibitions, and Stages in Saibatin Traditional Marriage: An Ethnographical and Legal Study - Widiyanti, Alzahra (Terekam Jejak Publisher, 2025)
This study discusse s the structure , prohibitions, and stage s of Saibatin customary marriage in Lampung as part of a sustainable customary le gal syste m. Using a normative and e thnographic juridical approach through inte rvie ws, lite rature studie s, and fie ld docume ntation, it was found that Saibatin customary marriage include s the matudau (hone st) and se me nda syste ms, with prohibitions re late d to kinship and social status. The stage s include pre -marriage , the main ce re mony, and the closing with the awarding of the adok title . Its imple me ntation is in line with national law as long as it doe s not conflict with Law No. 1 of 1974. Saibatin customs function not only as a cultural tradition, but also as a le gal syste m that maintains harmony and moral value s ​​in Lampung socie ty.